2009
DOI: 10.1093/jpepsy/jsp064
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Issues in Eating Pathology and Body Image Among Children and Adolescents

Abstract: Eating pathology and body image issues are now recognized as affecting all racial and ethnic groups. This article reviews eating pathology and body image concerns in four diverse groups in the U.S. (African Americans, Latino/as, Asians, and Native Americans). The major conclusion based on this review is that eating disturbances and body dissatisfaction occur to some degree in children and adolescents from all four major ethnic groups in the U.S; however, there is substantial variability across studies. Future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 75 publications
1
42
1
5
Order By: Relevance
“…Less is known about eating disturbances and BD in Asian American women because there are mixed findings about the differences between Asian American women and European American women (George & Franko, 2010). However, there seem to be more similarities than differences.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about eating disturbances and BD in Asian American women because there are mixed findings about the differences between Asian American women and European American women (George & Franko, 2010). However, there seem to be more similarities than differences.…”
Section: Discussionmentioning
confidence: 99%
“…(2014) con niños brasileños (6) reportó una insatisfacción corporal del 71,4%. Esta diferencia puede deberse a las variaciones culturales entre los países comparados, ya que si bien está establecido que las patologías alimentarias y los problemas asociados a la imagen corporal afectan a todos los grupos raciales y étnicos (34), se podrían generar diferencias relacionadas al contexto socioeducativo en el que se desenvuelven los niños, debido a que las provocaciones verbales de bullying acerca del peso pueden ser un predictor de insatisfacción corporal (35). Mikolajczyk y cols.…”
Section: Discussionunclassified
“…Cultural ideals influence how people assess their body image and body weight (Swami, Fredrick, Aavik, Alcalay, Allik, & Anderson 2010;Duda, Jumah, Hill, Seffah, Biritwum, 2007). A major issue associated with overweight and obesity is the perception of body size in different cultural settings (George & Franko 2010;Wardle, Haase, & Steptoe, 2006). It is also confirmed by Ross (1994) that the individuals' opinions of themselves are a reflection of the way that others perceive them.…”
Section: Sociodemographic Correlates Of Bmi Categories Among Female Umentioning
confidence: 99%
“…A major issue associated with overweight and obesity is the perception of body size in different cultural settings (George et al, 2010;Wardle, et al 2006). Our study used a questionnaire of body images to estimate self-reported body size and a scale to measure the BMI.…”
Section: Sociodemographic Correlates Of Bmi Categories Among Female Umentioning
confidence: 99%